Dari Sekolah Kolonial (Kweekschool) ke Gerakan Nasional: Politik Etis dan Pengaruhnya terhadap Transformasi Sosial di Indonesia - Nurhakim, Habib Akbar; Pramuharam, Annas Ma’ruf; Birsyada, Muhammad Iqbal (Jurnal Sejarah Citra Lekha, 2024)
This article aims to: (1) explain the ethical politics and the origins of the Kweekschool establishment policy; (2) analyze the educational system and programs offered at Kweekschool; (3) examine the influence of Kweekschool on the social transformation of the native (bumiputra) community. This study employs a historical research method. The findings indicate that: (1) The ethical politics, formalized by Queen Wilhelmina in 1901, led to the implementation of the Kweekschoolplan in 1927, which facilitated the establishment of Kweekschool as a response to the need for local teachers; (2) Kweekschool offered various educational programs aimed at training different categories of teachers, including those for rural schools and for Vervolg schools; (3) The ethical politics contributed to a social transformation within the bumiputra community, as Kweekschool graduates, who formed the educated elite, played a significant role in the emergence of nationalist movements that contributed to Indonesia's struggle for independence.